Oxygen Requirements of the Food Spoilage Yeast Zygosaccharomyces bailii in Synthetic and Complex Media - Rodrigues, Fernando (American Society for Microbiology, 2001)
Most yeast species can ferment sugars to ethanol, but only a few can grow in the complete absence of oxygen. Oxygen availability might, therefore, be a key parameter in spoilage of food caused by fermentative yeasts. In this study, the oxygen requirement and regulation of alcoholic fermentation were studied in batch cultures of the spoilage yeast Zygosaccharomyces bailii at a constant pH, pH 3.0. In aerobic, glucose-grown cultures, Z. bailii exhibited aerobic alcoholic fermentation similar to that of Saccharomyces cerevisiae and other Crabtree-positive yeasts. In anaerobic fermentor cultures grown on a synthetic medium supplemented with glucose, Tween 80, and ergosterol, S. cerevisiae exhibited rapid exponential growth. Growth of Z. bailii under these conditions was extremely slow and linear. These linear growth kinetics indicate that cell proliferation of Z. bailii in the anaerobic fermentors was limited by a constant, low rate of oxygen leakage into the system. Similar results were obtained with the facultatively fermentative yeast Candida utilis. When the same experimental setup was used for anaerobic cultivation, in complex YPD medium, Z. bailii exhibited exponential growth and vigorous fermentation, indicating that a nutritional requirement for anaerobic growth was met by complex-medium components. Our results demonstrate that restriction of oxygen entry into foods and beverages, which are rich in nutrients, is not a promising strategy for preventing growth and gas formation by Z. bailii. In contrast to the growth of Z. bailii, anaerobic growth of S. cerevisiae on complex YPD medium was much slower than growth in synthetic medium, which probably reflected the superior tolerance of the former yeast to organic acids at low pH.